2014
DOI: 10.1139/cjc-2013-0521
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of low-oxidation state tin compounds: an overview of the benefits of combining DFT Theory and experimental NMR spectroscopy

Abstract: The reactivity and complexation properties of dicoordinated Sn(II) and Sn(0) compounds are reviewed. The (dominant) electrophilicity of the stannylenes was confirmed and quantified through density functional theory (DFT) based reactivity indices. For these compounds, combining theoretical DFT calculations and experimental nuclear magnetic resonance (NMR) spectroscopic results has evidenced their potential to undergo -complexation from aromatic clouds in addition to significantly stronger -complexation. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 181 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…The purpose of this conference was to bring together researchers whose interests span the chemistry of germanium, tin, and lead, and this collection of manuscripts reflects the diverse range of topics presented at the conference: from the synthesis of low coordinate molecules as illustrated in the work presented by Jones 1 and studies of the reactivity of these interesting species as reported by Růžička, 2 Tokitoh 3 Willem, 4 and Baines 5 to the synthesis of high coordinate supramolecular structures as demonstrated in the work of Reuter; 6,7,8 from muon spin spectroscopy of germanium radicals as studied by West 9 to nuclear magnetic resonance spectroscopy 4 of Sn(II) and Sn(0) complexes; from the synthesis of ternary metal clusters as reported by Molloy 10 to polymers and their model oligomers as synthesized by Foucher 11 and Weinert, 12 respectively. Saito, 13 Shankar, 14 and Uhlig 15,16 describe their research on the high yielding synthesis and extended structures of several important functional tin(IV) compounds.…”
mentioning
confidence: 99%
“…The purpose of this conference was to bring together researchers whose interests span the chemistry of germanium, tin, and lead, and this collection of manuscripts reflects the diverse range of topics presented at the conference: from the synthesis of low coordinate molecules as illustrated in the work presented by Jones 1 and studies of the reactivity of these interesting species as reported by Růžička, 2 Tokitoh 3 Willem, 4 and Baines 5 to the synthesis of high coordinate supramolecular structures as demonstrated in the work of Reuter; 6,7,8 from muon spin spectroscopy of germanium radicals as studied by West 9 to nuclear magnetic resonance spectroscopy 4 of Sn(II) and Sn(0) complexes; from the synthesis of ternary metal clusters as reported by Molloy 10 to polymers and their model oligomers as synthesized by Foucher 11 and Weinert, 12 respectively. Saito, 13 Shankar, 14 and Uhlig 15,16 describe their research on the high yielding synthesis and extended structures of several important functional tin(IV) compounds.…”
mentioning
confidence: 99%